Laser-induced breakdown spectroscopy (LIBS), part I: review of basic diagnostics and plasma-particle interactions: still-challenging issues within the analytical plasma community - Hahn, David W; Omenetto, Nicoló (Applied spectroscopy, 2010)
Laser-induced breakdown spectroscopy (LIBS) has become a very popular analytical method in the last decade in view of some of its unique features such as applicability to any type of sample, practically no sample preparation, remote sensing capability, and speed of analysis. The technique has a remarkably wide applicability in many fields, and the number of applications is still growing. From an analytical point of view, the quantitative aspects of LIBS may be considered its Achilles' heel, first due to the complex nature of the laser-sample interaction processes, which depend upon both the laser characteristics and the sample material properties, and second due to the plasma-particle interaction processes, which are space and time dependent. Together, these may cause undesirable matrix effects. Ways of alleviating these problems rely upon the description of the plasma excitation-ionization processes through the use of classical equilibrium relations and therefore on the assumption that the laser-induced plasma is in local thermodynamic equilibrium (LTE). Even in this case, the transient nature of the plasma and its spatial inhomogeneity need to be considered and overcome in order to justify the theoretical assumptions made. This first article focuses on the basic diagnostics aspects and presents a review of the past and recent LIBS literature pertinent to this topic. Previous research on non-laser-based plasma literature, and the resulting knowledge, is also emphasized. The aim is, on one hand, to make the readers aware of such knowledge and on the other hand to trigger the interest of the LIBS community, as well as the larger analytical plasma community, in attempting some diagnostic approaches that have not yet been fully exploited in LIBS.